A mathematical model to predict early quality attributes in hake during storage at low temperature. (April 2018) - Vilas, C.; Alonso, A.A.; Herrera, J.R.; Bernárdez, M.; García, M.R.
Abstract: In this work we develop a model describing the evolution of the adenosine triphosphate (ATP) degradation products, typically used as early indicators of fish quality loss, during storage and transport conditions. The model is constructed following a modular approach that includes essentially three mechanisms: (1) enzymatic transformation of inosine 5′-monophosphate (IMP), inosine (Ino) and hypoxanthine (Hx) with some reactions catalyzed by bacteria; (2) bacterial growth and (3) nucleotide diffusion through the food matrix. This approach allows us to combine the different underlying mechanisms to account for other fish species and conditions. We compare alternative mechanisms explaining the catalytic effect of Pseudomonas and Shewanella populations on the reaction linking IMP, Ino and Hx. The selection is carried out in terms of the Akaike Information Criteria. The predictive capabilities of the selected model are demonstrated with experiments. Highlights: We study different dynamic models describing nucleotide degradation in fresh fish. We explore the influence of bacteria on several degradation routes. Models are calibrated and the best one is selected in terms of Akaike Criteria. We provide evidence that the transformation from IMP to Ino is catalyzed by bacteria.